1999
DOI: 10.1093/ajcn/69.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the glycemic index and content of indigestible carbohydrates of cereal-based breakfast meals on glucose tolerance at lunch in healthy subjects

Abstract: Glucose tolerance can improve in a single day. Slow absorption and digestion of starch from the breakfast meal, but not the content of indigestible carbohydrates in the breakfast meal, improved glucose tolerance at the second meal (lunch).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
4
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 24 publications
12
133
4
2
Order By: Relevance
“…There was a significant increase in GLP-1 concentration with a significant fall in gastric emptying rate and a decrease in postprandial glucose. These effects agree with the reports of decrease glucose and insulin and decrease in gastric emptying from the sodium propionate enrichment of bread (Liljeberg et al, 1999b). GLP-1 is known to have effects on gastric empting Figure 1 Circulating plasma glucose, insulin and GLP-1 response to four pasta-based test meals in healthy volunteers (n ¼ 9).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was a significant increase in GLP-1 concentration with a significant fall in gastric emptying rate and a decrease in postprandial glucose. These effects agree with the reports of decrease glucose and insulin and decrease in gastric emptying from the sodium propionate enrichment of bread (Liljeberg et al, 1999b). GLP-1 is known to have effects on gastric empting Figure 1 Circulating plasma glucose, insulin and GLP-1 response to four pasta-based test meals in healthy volunteers (n ¼ 9).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have demonstrated that the addition of viscous, soluble fibers, like psyllium, to food slows carbohydrate absorption and improves glucose regulation (Jenkins & Jenkins 1985a;Wolever et al, 1991). The inclusion of short chain fatty acids, eg lactic, acetic acid and sodium propionate, to carbohydrate-based products reduces glycemia and insulin demand (Liljeberg et al, 1999a). The addition of butter to potatoes decreases postprandial glycemia (Gannon et al, 1993), as does the addition of fat to pasta (Normand et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, a supplementation of the bread meal with 400 ml milk further increased the insulin demand. The spaghetti product used in the present study has previously been characterised regarding the postprandial glycaemic and insulinaemic responses, and was found to have a low GI and II (GI ¼ 52, II ¼ 42; Liljeberg et al, 1999). These favourable characteristics could be seen in the present study when comparing the bread þ water and spaghetti þ water meals (Table 2).…”
Section: Milk As a Supplement May Elevate Postprandial Insulinaemia Hsupporting
confidence: 61%
“…To what extent the second meal effect might be influenced by the rate of carbohydrate digestion or by fermentable carbohydrate is uncertain. To address this question, Liljeberg et al (1999) conducted a series of experiments in which comparisons were made between high fibre/low fibre breads, spaghetti and bread (similar fibre contents), and bread with and without a spread of raw potato starch. The results showed that the content of fermentable carbohydrates did not influence glycaemia after the second meal.…”
Section: Second Meal Effectmentioning
confidence: 99%